A transactional framework for pediatric rehabilitation: shifting the focus to situated contexts, transactional processes, and adaptive developmental outcomes. Issue 15 (17th July 2018) - King, Gillian; Imms, Christine; Stewart, Debra; Freeman, Matt; Nguyen, Tram
Abstract: Purpose: A paradigm shift is taking place in pediatric rehabilitation research, practice, and policy – a shift towards the real-life contexts of clients rather than requiring clients to navigate the world of pediatric rehabilitation. This article proposes a conceptual framework to bring about a broader awareness of clients' lives and transactional processes of change over the life course. Method: The framework draws attention to transactional processes by which individuals, situated in life contexts, change and adapt over the life course and, in turn, influence their contextual settings and broader environments. This framework is based on (a) basic tenets derived from foundational theories taking a life course perspective to change, and (b) transactional processes identified from relevant pediatric rehabilitation models that bring these foundational theories into the pediatric rehabilitation sphere. Results: The framework identifies three types of transactional processes relevant to pediatric rehabilitation: facilitative, resiliency, and socialization processes. These processes describe how contexts and people mutually influence each other via opportunities and situated experiences, thus facilitating capacity, adaptation to adversity, and socialization to new roles and life transitions. Conclusions: The utility of the framework is considered for research, practice, service organizations, and policy. Implications for Rehabilitation: The framework supports practitioners going beyond person and environment as separate entities, to provide services to the "situated person" in real-life contexts The framework shifts the focus from "body structures/functions" and "person in activity" to "person in changing and challenging life contexts" Working from a transactional perspective, practitioner-client conversations will change; practitioners will view client situations through a lens of opportunities and experiences, assess client experiences in real-life contexts, and strive to create context-based therapy opportunities The framework suggests the benefit of greater focus on resiliency processes to support client self-efficacy, self-determination, and autonomy, and socialization processes to enhance ability to enact new life roles at times of transition